LATIN LANGUAGE AND ITS STUDY IN THE MODERN WORLD - Kenjayeva Nigora Davladovna (Journals Park Publishing, 2024)
This article explores the critical role played by historical sources in the study of the Latin language, emphasizing their significance in unraveling linguistic evolution, cultural nuances, and societal dynamics. Focusing on various types of sources, including literary texts, inscriptions, legal documents, and personal correspondences, the article delves into the linguistic analysis and structural features inherent in each category. The examination of syntactical and grammatical structures, along with the exploration of lexical variations and the cultural context embedded in historical sources, provides a comprehensive understanding of Latin across different genres and periods.
Keywords: lingua Latina, Romance languages, types of historical sources, linguistic evolution in literary texts.